Job satisfaction, marital conflict and marital quality in later years of marriage. - Sahrani, Syah Qurratu Aini; Juhari, Rumaya; Yaacob, Siti Nor (2012)
Marital duration has been identified as one of the factors that may influence marital satisfaction. Research on marital quality had become prior concern in the marriage research field. Unfortunately, less research had focus on Muslim couples. The present study aims to explore the marital quality among married Muslims individuals in later years of marriage. One hundred and eighty (n = 180) individuals who have been married for at least 20 years were recruited in this study. Marital quality was assessed using Dyadic Adjustment Scale. Data were gathered in four different districts in Selangor. Results in this study showed that individuals who had been married for at least 20 years tend to have more stable and high marital quality. Score for each subscale were analyzed and further discussed in this article. Future studies using longitudinal approaches are needed in order to better understand the influence of marital duration on marital quality and how marital conflict developed and managed across the years.